Family Benefit Reform in Lithuania: Microsimulation of Its Distributional Impacts - Salanauskaitė, Lina; Verbist, Gerlinde (Lithuanian Journal of Statistics, 2013)
The paper explores to what extent the Lithuanian family benefit system is able to reduce inequality and poverty among families with children, with poverty reduction being one of the major aims. Family benefits underwent a major reform in2004, which entailed a shift from means-tested benefits to a more universal system. Due to budget constraints, the implementation of the full reform design has been postponed until 2008. No distributional impact analysis of this reform, either of its initial or of its final designs, has been implemented yet. Furthermore, we analyse whether the gains from the newly designed system of family benefits are not outweighed by respective losses in social assistance benefits. To conduct such an analysis, we develop a partial static microsimulation model based on the EU-SILC (household income and living conditions) survey. The model is programmed in STATA statistical software. Our findings show that, despite small income improvements brought by the reform, its overall child poverty reduction effectiveness is limited. Moreover, the interaction of a family benefit with the social assistance system implies that some household types are relatively “bigger” winners compared to others. For example, our research reveals that single-parent households would obtain income gains comparable to those of large families only when the full reform scenario is implemented. If considering indirect effects (i.e. the loss of social assistance benefits), their relative gains become even smaller.
Keywords: microsimulation; EU-SILC survey; family benefits; poverty and inequality indicators